Inklusionen und Exklusionen des Humanen - Holtmann, Sophie C.; Hascher, Philipp; Stein, Roland (Verlag Julius Klinkhardt, 2019)
In social debates about inclusion, the humane, the individual person, runs the risk of being lost from view, as the discussions are often only conducted on a systemic-structural level. However, aspects of concrete pedagogical and conceptual work and educational encounters are also affected. This volume is dedicated to the diversity of individuals in their respective contexts in the spectrum between inclusions and exclusions from different theoretical and practical perspectives. From everyday situations in German and American classrooms to school inclusion models and the Federal Participation Act to humane exclusions in the internationally networked digital age; from discourses on vulnerability, ethics and exclusion to the topos of the stranger in the educational inclusion debate, multiple perspectives open up.